Prioritization and Timing of Outcomes and Endpoints After Aneurysmal Subarachnoid Hemorrhage in Clinical Trials and Observational Studies: Proposal of a Multidisciplinary Research Group - Stienen, Martin N.; Visser-Meily, Johanna M.; Schweizer, Tom A.; Hänggi, Daniel; Macdonald, R. Loch; Vergouwen, Mervyn D. I. (Neurocritical care, 2019)
Introduction In studies on aneurysmal subarachnoid hemorrhage (SAH), substantial variability exists in the use and timing of outcomes and endpoints, which complicates interpretation and comparison of results between studies. The aim of the National Institute of Health/National Institute of Neurological Disorders and Stroke/National Library of Medicine Unruptured Intracranial Aneurysm (UIA) and SAH common data elements (CDE) Project was to provide a common structure for future UIA and SAH research. Methods This article summarizes the recommendations of the UIA and SAH CDE Outcomes and Endpoints subgroup, which consisted of an international and multidisciplinary ad hoc panel of experts in clinical outcomes after SAH. Consensus recommendations were developed by review of previously published CDEs for other neurological diseases and the SAH literature. Recommendations for CDEs were classified by priority into “Core,” “Supplemental—Highly Recommended,” “Supplemental,” and “Exploratory.” Results The subgroup identified over 50 outcomes measures and template case report forms (CRFs) to be included as part of the UIA and SAH CDE recommendations. None was classified as “Core”. The modified Rankin Scale score and Montreal Cognitive Assessment were considered the preferred outcomes and classified as Supplemental—Highly Recommended. Death, Glasgow Outcome Scale score, and Glasgow Outcome Scale-extended were classified as Supplemental. All other outcome measures were categorized as “Exploratory”. We propose outcome assessment at 3 months and at 12 months for studies interested in long-term outcomes. We give recommendations for standardized dichotomization. Conclusion The recommended outcome measures and CRFs have been distilled from a broad pool of potentially useful CDEs, scales, instruments, and endpoints. The adherence to these recommendations will facilitate the comparison of results across studies and meta-analyses of individual patient data.